Recurrence of Cholesteatoma - A Retrospective Study Including 1,006 Patients for More than 33 Years - Møller, Patrick Rønde; Pedersen, Christina Nygaard; Grosfjeld, Line R.; Faber, Christian E.; Djurhuus, Bjarki D. (International Archives of Otorhinolaryngology, 2020)
Introduction Cholesteatomas are benign tumors consisting of skin, and growing inside a retraction pocket in the tympanic membrane. Cholesteatomas can occupy the entirety of the middle ear, and are known for their osteolytic capabilities. Surgery is the only curative treatment for cholesteatomas.Objective To describe the risk of recurrence after first-time surgically-treated middle-ear cholesteatoma (STMEC1) on the island of Funen from 1983 to 2015.Methods Cases of STMEC1 were identified in the Danish National Hospital Register. The medical records were reviewed. Time-to-event analyses were applied. The ears were followed from STMEC1 to a secondary cholesteatoma, emigration, death, or end of follow-up.Results Records from 1,006 patients with STMEC1 were reviewed. A total of 54 patients were submitted to surgery on both ears. The total sample consisted of 1,060 ears with STMEC1; 300 were children's (< 16 years) ears, and 760 were adult's ears. The total observation time was of 12,049 years.The overall estimated proportion with recurrence 5 years after surgery was of 37% in children and of 15% in adults. The older the child was at the first surgery, the risk decreased by 7% per year. In children, canal wall up (CWU) mastoidectomy without obliteration was associated with a hazard ratio for recurrence of 1.9 (95% confidence interval [95%CI]: 1.2–3.0) compared with CWU with obliteration.Conclusion Compared with adults, children were had 2.6 times more risk of recurrence. Procedures performed without mastoidectomy had the lowest risk of recurrence. In children, obliteration was associated with a significantly lower risk of recurrence. However, patients were not randomized regarding the surgical approach; thus, the association between approach and risk of recurrence was likely influenced by confounding factors.
Keywords: cholesteatoma; recidivism; recurrence; surgery; middle ear